Determinação da ativação de monócitos e de biomarcadores celulares em gestantes portadoras de pré-eclâmpsia - Romão, Mariana [UNESP] (2013)
Preeclampsia (PE) is a pregnancy-specific human syndrome characterized by a systemic inflammatory response, with higher intensity than the one observed in normal pregnancy. In this pathology, innate immune cells such as monocytes and granulocytes are activated endogenously and secrete high levels of inflammatory cytokines and free radicals. 1) to determine the activation state of monocytes by endogenous expression of TLR2 and TLR4 receptors as well as the nuclear transcription factor (NF-κB) activation in these cells in pregnant women with PE, distributed according to the gestational age of clinical manifestations (early or late-onset) of the disease; 2) to correlate TLR2 and TLR4 expression with TNF-α, IL-10 and IL-12 by monocytes stimulated with lipopolysaccharide (LPS) of Escherichia coli and peptidoglycan (PGN) of Gram-positive bacteria in pregnant women with early-onset or late-onset PE; 3) to verify if the parameters studied may differentiate early-onset or late-onset PE. We studied 92 pregnant women, 32 normotensive and 60 women with PE, paired for gestational age. Preeclamptic pregnant women were classified according to onset of clinical manifestations in early-onset PE (<34 weeks gestation, n=30) and late-onset PE (≥ 34 weeks gestation, n=30). Monocytes from peripheral blood obtained from preeclamptic and normotensive pregnant women were incubated for 18h in the absence or presence of LPS or PGN. Expression of TLR2 and TLR4 receptors present on the surface of monocytes, was detected by flow cytometry, using specific monoclonal antibodies labeled with fluorochromes. To analyze NF-κB, monocytes were incubated with or without LPS or PGN for 30 min and the nuclear extract obtained was employed for NF-κB determination. Monocytes were further cultured in the presence or absence of LPS and PGN and the supernatant obtained after 18h cultivation was aspirated and used for TNF-α, IL-10, IL-12p40 and IL-12p70 determination by ...